Do Fear of Missing-out Mediated by Social Media Addiction Influence Academic Motivation Among Emerging Adulthood? - Rahma Widyana; Santi Esterlita Purnamasari (Universitas Ahmad Dahlan, 2020)
AbstractÂ The aim of this research was to examine the relationship between fear of missing out and academic motivation mediated by social media addiction among emerging adulthood. The participants involved in this research were 18 to 25 years emerging adulthood, who live in Special Region of Yogyakarta. They were active internet users and have used the internet for more than 6 months. Furthermore, they were students in both high school and university. The hypothesis proposed in this study was that there is a relationship between fear of missing out and academic motivation mediated by social media addiction. The results showed that the hypothesis was correct. This implies that the fear of missing out is negatively correlated with academic motivation mediated by social media addiction. However, it was discovered that there was a positive correlation between fear of missing out and social media addiction. There was also a negative correlation between social media addiction and academic motivation.Keywords: social media addiction, fear of missing out, academic motivation, emerging adulthood